Assessing flexibility in event-driven process adaptation. (March 2019) - Patiniotakis, Ioannis; Apostolou, Dimitris; Verginadis, Yiannis; Papageorgiou, Nikos; Mentzas, Gregoris
Abstract: Business process management (BPM) has emerged as a prominent information management approach focusing on the design, execution and governance of organizational business processes. The ability to deal with both foreseen and unforeseen changes in business processes is considered critical for contemporary business process management systems. This paper proposes an approach that couples an event-driven framework for detecting and reasoning in situations that pose the need for process adaptations with MCDM methods for selecting adaptations. The proposed approach has been implemented in an aspect-oriented extension of a BPMN2.0 engine in order to enact adaptations of business processes in real-time. Highlights: We assess flexibility in event-driven adaptive processes using an aspect-oriented approach and a dynamic mechanism for selecting adaptations. We evaluate the benefits and limitations of our approach by implementing it in BPMN2.0 workflow engine.